Study of zinc and lead addition effect on structure-properties of phosphate glasses. (2019) - Abid, M.; Belfaquir, M.; Hafid, M.; Taibi, M.
Abstract: The purpose of this work was to study a range of phosphate-based glasses of two groups of glasses with compositions (35-y)Li2 O–yPbO–15ZnO–50P2 O5 (0≤y≤35 mol% of PbO) and (35-z)Li2 O–zZnO–15PbO–50P2 O5 (0≤z≤35 mol% of ZnO) containing a fixed amount of (50 mol%) of P2 O5, modified by the addition of PbO and ZnO respectively. Their thermal analysis, density, molar volume and infrared spectroscopy studies were conducted to compare the data obtained from both series glasses. Thermal analyses revealed a slight difference in the glass transition temperatures obtained between the two groups. The density values increased linearly with increasing PbO and ZnO contents for two series, whilst the molar volume decreases non-linearly with ΔVm = 2, 39 cm 3 /mol for the addition of PbO and ΔVm = 5, 94 cm 3 /mol for the addition of ZnO. FT-IR spectra reveal the formation of P–O–Pb and P–O–Zn bonds in these glasses and show that metaphosphate network is not affected when PbO and ZnO contents increase in both groups. Thus, PbO and ZnO are assumed to play an intermediate role in a way that Pb 2+ and Zn 2+ cations tend to break P–O–P bonds forming PbO4 and ZnO4 units with covalent Pb–O and Zn–O bonds. The predominant structural units in both series glasses are metaphosphate (P2 O6 ) 2- groups